Doctor-patient relationship (Pulse, 2010)
The doctor-patient relationship is central to the practice of medicine and is essential for the delivery of high-quality health care in the diagnosis and treatment of diseases. The patients must have confidence in the competence of doctors and should feel that they can confide in him or her. For physicians, the establishment of a good rapport with the patients is also important. This being said, some medical specialties, emphasize more on the doctor-patient relationship than others. The doctor-patient relationship forms one of the foundations of contemporary medical ethics.DOI: 10.3329/pulse.v3i1.6546Pulse Vol.3(1) July 2009 p12-14